Implementasi Regulasi Hukum Ekonomi Syariah dalam Pencegahan Perjudian Online Remaja: Analisis Tantangan dan Strategi Pengembangan - Nurul Ahda Suviani; Hermawati; Muliani (Prodi Hukum Ekonomi Syariah (Muamalah), 2025)
This research aims to analyse the challenges and prospects of sharia economic law regulation of online gambling among teenagers. This research uses a normative-juridical approach from the perspective of sharia economic law, a qualitative library research method that is descriptive-analytical in nature. The research data sources consist of primary data and secondary data, data collection through purposive sampling documentation studies and systematic literature searches on Google Scholar. Data analysis uses content analysis with a thematic approach, coding and categorisation based on themes, validation through source triangulation and cross-checking literature. The results show that sharia economic law regulation has promising prospects in the prevention of youth online gambling by utilising blockchain technology for transparency and artificial intelligence preventive monitoring systems, as well as the development of a holistic regulatory framework that integrates five pillars: normative, preventive, educative, restorative, and collaborative. This research contributes to formulating more effective regulatory strategies to protect teenagers from the negative impacts of online gambling, as well as promoting sustainable social and economic justice in accordance with the principles of sharia law, especially in filling a significant research gap in the field of sharia economic studies on the phenomenon of teenage online gambling.